Homoeopathic Awareness among the Tribal Population Visiting a Homoeopathic Hospital set up in West Bengal - Mukherjee, Anupam; Banerjee, Ayushman; Das, Kaushik D. (Homœopathic Links, 2019)
Background Tribal population in India had been known to depend on traditional tribal medicines for long to cure their ailments. With the development of health care facilities and spread of AYUSH system:of late many tribal people are seeking homoeopathic treatment. More than half of the tribal population of West Bengal are concentrated in the South western part of the state that covers the districts of Paschim Medinipur, Purulia, and Bankura. Midnapore Homoeopathic Medical College and Hospital being located in the same region gets a good number of tribal patients seeking homoeopathic care.Objective To assess the level of homoeopathic awareness and the reasons for their preference to homoeopathic system.Methods A cross sectional survey was conducted in the outpatient department of Midnapore Homeopathic Medical College and Hospital, Government of West Bengal, India from January 2016 to June 2016 on adult tribal population using a self-administered questionnaire.Results The survey performed on tribal patients reflected the level of homoeopathic awareness, prevalence of disease, socio-demographic data, and health status of the tribal population. The positive effect with homoeopathic treatment also became evident in the study.Conclusion A favorable attitude toward homoeopathy among the tribal population was obtained. However, some wrong notions about the mode also emerged in the study. In this respect, the authors felt the need on arrangement of homoeopathic health camps and distribution of homoeopathic awareness materials in tribal language to improve the scenario.
Keywords: homoeopathy; homoeopathic awareness; traditional tribal medicine